Inovasi Strategik dalam Layanan Terapi ABA sebagai Alternatif Pendidikan untuk Anak Autis di Luar Sekolah Formal - Suherman, Maman; Aryani, Wiwik Dyah; Nurohmah, Sherly; Lubna, Fadhillah (Jurnal Pendidikan Kebutuhan Khusus, 2025)
This study aims to examine strategic innovations in ABA therapy services as an alternative to formal out-of-school education. Using descriptive qualitative methods, data were collected through observation, interviews and documentation involving therapists, parents and professionals. The results showed that ABA therapy is effective in improving autistic children's abilities, especially when supported by a gradual learning program, the use of digital technology, parental involvement, and interprofessional collaboration. However, there are still challenges such as limited access to services and training for families. Therefore, strategic innovations are needed to make ABA therapy more effective, sustainable and suitable for the needs of the whole child.